The human body life story - Discovery Channel (USA : Discovery Channel School, 2003)
Overviewing the development of the human body- through time and throught lifetime, with stunning footage that reveals how our circulatory, cardiovascular and neurological systems work
Executive producer, Adrienne Schure; production manager, Olivia Foster
Keywords: Body, Human